Integrated data analysis model for screening cell line producer - Mohamed Azmin, Nor Fadhillah (Springer Nature, 2018)
The complexity of bioprocess data generated from the manufacture of recombinant monoclonal antibodies cell line sparks the chemometrics study of the datasets. The ultimate goal is to form a link between the data and its underlying biological patterns. A concatenated protocol, specifically discrete wavelet transform and multiway principal component analysis techniques, is recommended to successfully extract meaningful information from the complex datasets.